2018 KLEIN LECTURE: INDIVIDUAL AND AGGREGATE LABOR SUPPLY IN HETEROGENEOUS AGENT ECONOMIES WITH INTENSIVE AND EXTENSIVE MARGINS. (30th November 2018) - Chang, Yongsung; Kim, Sun‐Bin; Kwon, Kyooho; Rogerson, Richard
Abstract: We study business cycle fluctuations in heterogeneous agent general equilibrium models featuring intensive and extensive margins of labor supply. A nonlinear mapping from time devoted to work to labor services generates operative extensive and intensive margins. Our model captures the salient features of the empirical distribution of hours worked, including how individuals transit within this distribution. We study how various specifications influence labor supply responses to aggregate technology shocks and find that abstracting from intensive margin adjustment can have large effects on the volatility of aggregate hours even if fluctuations along the intensive margin are small.